Determinants of Student Career Adaptability: A Study by Gender, Parental Income, and Major in High School - Alamsyah, Muh. Nur; Rahman, Diniy Hidayatur; Zamroni, Zamroni; Yasin, Alwyn (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: This study aims to describe the career adaptability of students at SMA Negeri 5 Jeneponto. The sample size consisted of 83 tenth grade (X) and eleventh grade (XI) students selected using simple random sampling technique. Data collection was conducted using a career adaptability scale adapted from the Career Adapt-Abilities Scale (CAAS) by Savickas. The results of the analysis showed that the average score of students' career adaptability reached 77.72, which indicated that the career adaptability of students in this study was high. The majority of the research subjects rated that they had good career adaptability. Based on this finding, it can be concluded that the students who were the research subjects had a high level of career adaptability. Additional analysis showed that there were no significant differences in students' career adaptability based on gender, parental income, and chosen major. Students showed strong confidence in making career choices, actively sought information about careers of interest, cared about planning their career futures, and took responsibility for the steps they took in their careers. In conclusion, students who are the subjects of this study have a high level of career adaptability, without being influenced by these demographic variables. Keywords: high school student profile, career adaptability, gender, parental income, major.